Implementation of E-Government Through Myceisa Application in Covid-19 Era (Case Study of Customs and Excise Supervision and Service Office of Customs Type C Meulaboh) - Manurung, Pebriyanti (Journal of Political and Governance Studies, 2025)
Background : Active involvement in the information, communication, and technology revolution has led many central and local government agencies to develop public services through communication and information technology, known as e-government. This research is to examine the implementation of one form of e- government, namely the MyCeisa application at the Customs and Excise Supervision and Service Office Type C Meulaboh Customs. This study also discusses the challenges and support in its implementation as well as suggestions for solving all the challenges faced. Methods: This study uses a qualitative method with a descriptive approach. In collecting data, the author uses the method of observation, interviews, documentation and audio documents and data analysis techniques using the methods of reduction, presentation and drawing conclusions. Results The results of the study indicate that the implementation of the MyCeisa application has been carried out well as evidenced by the fulfillment of all indicators of successful policy implementation based on the theory of successful policy implementation of Edward III. The challenges faced in its implementation are the MyCeisa application server which is sometimes down and the internet network is also disrupted during a power outage. Meanwhile, support during the implementation of the MyCeisa application includes competent and quality human resources, an easy MyCeisa application work system and facility assistance and support from related agencies. Conclusions The implementation of the MyCeisa application has been successful, supported by competent and high-quality human resources, a user-friendly system, and assistance from related agencies.